Tudo ou tudo: a concretude e o luminoso na poética de Arnaldo Antunes - Oliveira, Daniele Gomes de [UNESP] (2015)
In t his thesis we discusst he work of Arnaldo Antunes critically creatively. Author 's works were studied in various art forms practiced by him as calligraphy, perfor mance, music, and writing. Here is the wor k of Arnaldo Antunes, in a context that opens the Transemiose